The development and validation of an UV-Vis spectrophotometric method for the determination of ciprofloxacin in raw material and dosage forms - Mavanga Mabaya, Timothé; Mankulu Kakumba, Jocelyn; Mayangi Makola, Mannix; Mbenza Puati, Adelard; Mana Kialengila, Didi; Mavar Tayey Mbay, Jean; Mbinze, Jeremie (Orapuh Journal, 2025)
Introduction The quality control of medicines is crucial for market surveillance worldwide. With the growing problem of counterfeit drugs, it is important to protect the population from substandard medicines and equip professionals with effective analysis tools. Analytical methods such as UV-Vis spectrometry offer advantages over techniques like HPLC, which require more expensive equipment and solvents, especially in developing countries. Purpose This study aimed to develop and validate a simple, precise, accurate, reproducible, and less expensive UV-Vis spectrophotometric method for determining ciprofloxacin HCl in its pure form and dosage forms. Methods An appropriate wavelength was selected by scanning a ciprofloxacin HCl standard solution in 0.1M hydrochloric acid between 200–400 nm. The absorption maximum at 277 nm was chosen for further analysis. The method was developed and validated according to ICH guidelines, evaluating criteria such as linearity, precision, accuracy, specificity/selectivity, robustness, LOQ, and LOD. Results Ciprofloxacin HCl showed maximum absorption at 277 nm, following Beer-Lambert’s law within the concentration range of 2.5 to 15 µg/ml. The linear regression equation was Y = 0.1104x, with a correlation coefficient of R² = 0.999. The LOD and LOQ were 0.4385 µg/ml and 1.4617 µg/ml, respectively. Intra- and inter-day precision had relative standard deviations under 2%, with recovery rates for selectivity (98.36–98.72%) and accuracy (100.10–100.83%) within acceptable ranges. Robustness standard deviations were below 2%, and ciprofloxacin levels in the samples ranged from 94.10% to 110%. Conclusion The validated method is suitable for routine quantification of ciprofloxacin HCl as raw API or in tablet forms, with revalidation needed for other pharmaceutical forms.